AMP-activated protein kinase: regulating cellular and whole body energy balance - Hardie, Grahame (Henry Stewart Talks, 2010)
AMPK-activated protein kinase, Role as a cellular energy sensor, Role in lower eukaryotes, Metabolic pathways targeted by AMPK, Cytokines, drugs (including metformin) and xenobiotics that target AMPK, Identification of upstream kinases, Regulation by AMP, ATP and calcium ions, Potential of AMPK as a drug target in cancer
Archived at 2021/11/28